Kesehatan dan Keselamatan Kerja (K3) terhadap Kinerja Karyawan - Titi Hasanah (Journal of Management and Bussines (JOMB), 2021)
This study aims to determine the effect of Occupational Health and Safety (K3) on Employee Performance. The number of samples is 76 respondents. Data were obtained from questions using a questionnaire consisting of closed and open questions. Respondents' answers were then analyzed by two-stage regression using the SPSS (Statistical Package for Social Science) version 22 analysis tool. Based on the analysis carried out, the regression coefficient Y = 4.741 + 0.325X1 + 0.563X2, which means if the occupational safety and health variables do not exist or equal to zero (0), then the employee's performance is 4.741. The T-test shows the significance value for the occupational health and safety variables, each of which is 0.000. The F test shows the significance value is 0.000. The conclusions obtained are as follows: a) occupational health and safety have a significant effect on employee performance; b) the occupational health and safety variables each have a significant influence on employee performance; c) the variables of occupational health and safety have a significant influence together on employee performance. Keywords: Occupational Health, Occupational Safety, Employee Performance